FACING CHALLENGES IN MULTIMEDIA ENTREPRENEURSHIP: KEYS TO SUCCESS IN THE DIGITAL ERA - Mohamad Arief (Jurnal Scientia, 2023)
In the increasingly developing digital era, multimedia businesses face various complex challenges. This research aims to identify the challenges faced by multimedia entrepreneurs in facing changes in the digital era and to identify the keys to success that can help them overcome these challenges. This research uses a descriptive analysis method by collecting data through interviews and surveys with a number of multimedia entrepreneurs operating in the digital era. The research results show that multimedia entrepreneurship in the digital era offers extensive opportunities, but is also faced with a number of challenges that must be overcome. Rapid technological developments, intense competition, and the expansion of appropriate business models are key factors in the success of multimedia businesses. Multimedia entrepreneurs need to focus on content innovation, smart monetization, and user experiences that meet expectations to generate stable revenues and build a strong reputation. With a deep understanding of multimedia technology, creativity, and a solid business strategy, multimedia entrepreneurship can be a profitable opportunity in the ever-evolving digital era. This research provides useful insights for multimedia entrepreneurs to face challenges in this digital era.